For the win : how game thinking can revolutionize your business - Werbach, Kevin, ....-; Hunter, Dan, ....- (Philadelphia : Warton digital press, 2012)
Video games now have the dubious honour of having inspired their own management craze. Called 'gamification,' it aims to take principles from video games and apply them to serious tasks. The latest book on the subject, For the Win, comes from Kevin Werbach and Dan Hunter, from the Wharton Business School and the New York Law School respectively...[T]heir central idea--that the world might be a better place if work was less of a necessary drudge and more of a rewarding experience in itself--is hard to argue with. --The Economist Here's a conversion worthy of a Transformers movie: Take buttoned-down, MBA-toting business professionals and turn them into video game designers. That's the goal of a new book about Gamification, changing behavior of employees and customers by appealing to their sense of fun and their competitive instinct, video game style. The co-author of For the Win: How Game Thinking Can Revolutionize Your Business is Dan Hunter, who runs New York Law School's Institute for Information Law and Society. He says gamification done right is about meaningful competition. --David Brancaccio, Marketplace, American Public Radio Werbach and Hunter aren't playing around with this book on how to add the joy of gaming to your enterprise. This is a quick but thoughtful look into the pros and cons of gamification, what works and what doesn't, with plenty of insight into what really motivates and engages customers and employees. --Daniel H. Pink, author of Drive and A Whole New Mind For the Win is a total win! In the 21st century, business must shift from push to pull to get the best out of their employees and to entice their customers. This book brilliantly explains how to design and use gamification techniques to that end.